Geometrical modeling of the process of weaving a wire cloth in weightlessness using the inertial unfolding of a dual pendulum - Kutsenko, Leonid; Semkiv, Oleg; Zapolsky, Leonid; Shoman, Olga; Kalynovskyi, Andrii; Piksasov, Mykhailo; Adashevska, Irina; Shelihova, Inessa; Sydorenko, Olena (ПП "Технологічний Центр", 2018)
We investigated a geometrical model of unfolding a rod frame of an orbital object as a process of oscillations of a multi-link pendulum under conditions of weightlessness and within an abstract plane. The initiation of oscillations is assumed to be driven by the pulse action on one of the nodal elements of the pendulum, implemented using a pulsed rocket engine. The transported (starting) position of a multilink pendulum shall be accepted in the “folded” form. A notation of the inertial frame unfolding is performed employing the Lagrange equation of the second kind, in which potential energy was not taken into consideration because of weightlessness. It was established in the course of research: – to unfold the structure, there is no need to synchronize the means of control over the magnitudes of angles in separate nodes; – transverse oscillations of nodes (tremor) before the moment of full unfolding of a multi-link pendulum can be used as signal for the actuation of locks in order to fix the position of its adjacent links; – based on a circuit for unfolding a single multi-link structure, it is possible to form multi-beam circuits with a shared non-movable attachment node (a triad as an example). Reliability of the obtained approximate solution was tested using the created animated film about the unfolding process of the structure. An example of a four-link pendulum was studied in detail. The results might prove useful when designing the unfolding of large-size structures under conditions of weightlessness, for example, frames for solar mirrors

Запропоновано спосіб виготовлення у невагомості металевого сіткополотна за допомогою коливань ряду подвійних маятників. Коливання виникають завдяки впливу на вузли елементів маятника імпульсів двох реактивних двигунів, тим самим забезпечуючи його інерційне розкриття. Опис процесу інерційного розкриття маятника виконано за допомогою рівняння Лагранжа другого роду. Результати доцільно використати при проектуванні масштабних сіткополотен, наприклад активних поверхонь антен довгохвильового діапазону, та їх виготовлення в умовах невагомості
Геометричне моделювання плетіння сіткополотна в невагомості за допомогою інерційного розкриття подвійного маятника
Keywords: multi-link pendulum; large-scale structure; deployment in cosmos; mirror in space; Lagrangian equation of the second kind; геометричне моделювання; сіткополотно; подвійний маятник; розкриття антени; рівняння Лагранжа другого роду